Perampanel Confirms to Be Effective and Well-Tolerated as an Add-On Treatment in Patients With Brain Tumor-Related Epilepsy (PERADET Study) - Coppola, Antonietta; Zarabla, Alessia; Maialetti, Andrea; Villani, Veronica; Koudriavtseva, Tatiana; Russo, Emilio; Nozzolillo, Agostino; Sueri, Chiara; Belcastro, Vincenzo; Balestrini, Simona; Ferlazzo, Edoardo; Giannarelli, Diana; et al. (Frontiers in Neurology, 2020)
Background: Epilepsy is one of the most common symptoms of brain tumors. It is often drug resistant and generally worsen patients’ quality of life (QoL). Brain tumors release glutamate among other mediators, contributing to seizures onset, and this is accompanied by an increased AMPA receptors’ expression on neuronal cells’ membrane. Perampanel (PER) is a relatively new antiseizure medication (ASM) that acts as a selective non-competitive AMPA receptors’ antagonist. Given its mechanism of action, we aimed to evaluate through a prospective, observational study, the efficacy and safety of PER as an add-on treatment in patients with brain tumor-related epilepsy (BTRE). The study was called PERADET. Methods: Thirty-six adult patients (intention to treat population-ITT) affected by BTRE, with uncontrolled focal-onset seizures treated with 1-3 ASMs were recruited from four Italian epilepsy centers. Perampanel was added-on, titrated from 2 mg/day up to a maximum of 12 mg/day. Tumor history and therapy, type and seizures frequency, previous ASMs were collected at 6 and 12 months. A battery of QoL tests were administered at baseline, 6 months and 12 months. The primary endpoint was to assess the efficacy of PER by calculating the percent change in seizure frequency and the responder rate. The secondary endpoints were tolerability, retention rate at 12 months and improvement in quality of life. Results: At the end of 12 months, 21 patients (per protocol population-PP) were available for evaluation. In this population the responder rate (percentage of patients who experienced a 50% or greater reduction in seizure frequency) was 90.4% with 33.3% of patients being seizure-free. In the ITT group the responder rate at the end of 12 months was 66.6% with 25% of patients being seizure free. PER was well tolerated (30.6% of patients experienced an adverse event, none was severe; three needed a treatment interruptions). Conclusions: Our study indicate that PER may be efficacious against BTRE as suggested by its mechanism of action and our current knowledge on mechanisms of brain tumor epileptogenicity. Trial Registration Number (TRN): (Prot. n° 0008872.25-06-2019); RS 919/17.